Experiences of women of childbearing age regarding Implanon provision in South Africa - Modiegi D. Motlhokodi; Thifhelimbilu I. Ramavhoya; Mmapheko D. Peu (AOSIS, 2023)
Background: The World Health Organization has stated that millions of women of childbearing age in developing countries who are not planning to be pregnant are not utilising modern contraceptives such as long-term contraceptives, including Implanon. South Africa had a high rate of women of childbearing age who used Implanon as one of long-term contraception methods from its introduction in 2014. Familiar reasons for women to not use modern contraceptives involved a lack of healthcare facilities, supplies and trained healthcare workers in their area to provide effective contraceptive services in South Africa. Aim: This study aimed to explore and describe the experiences of women of childbearing age regarding Implanon provision. Setting: The study was conducted in primary health care facilities of Ramotshere Moiloa subdistrict, South Africa. Methods: Qualitative, descriptive phenomenological approach was used in this study. Twelve women of childbearing age were purposively sampled. Childbearing age refers to woman in their reproductive ages who will not be regarded as high risk for pregnancy. Semi-structured interviews were utilised to collect data and five Colaizzi's steps of data analysis were used. Data were collected from 12 of 15 selected women of childbearing age who had experience in utilising Implanon contraceptive device. Data saturation was reached after interviewing 12 participants as the information was coming out, repeatedly. Results: Three themes with subthemes emerged from the study, namely period of Implanon use, experiences of obtaining information regarding Implanon and healthcare experiences related to Implanon. Conclusion: It was evident that a lack of effective pre- and post-counselling, eligibility screening and poor management of severe side effects are contributory factors that led to early removal and decline in uptake of the said method. There is also a lack of effective comprehensive Implanon training to some of reproductive service providers. Contribution: It may increase the number of women who still want to use Implanon as a reliable method.